2013
DOI: 10.1177/159101991301900119
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Distribution of Glioblastoma Multiforme at Diagnosis

Abstract: Treatment of high-grade gliomas with selective intra-arterial (IA) administration of chemotherapies has been proposed, and utilized as a therapeutic modality. This approach offers the conceptual benefit of providing maximal delivery of the agent to the tumor bed, while potentially reducing systemic exposure to the agent. This retrospective study was designed to determine the vascular distribution of glioblastoma multiforme (GBM) at the time of diagnosis in an effort to determine what proportion of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…With the development of microcatheters, IA delivery with distal cannulation of super-selective arteries is now possible; although this may reduce neurologic complications, this comes at the cost of increased streaming effects ( 48 ). In addition, drug delivery is limited to a more precise region, which may not reach the invasive malignant cells at the tumor edge, and only a small percentage (6%) of patients with glioblastoma have a single vessel identified as supplying the tumor ( 51 ). Because most adult malignant gliomas are supratentorial, intracarotid arterial administration techniques can be used.…”
Section: Circumventing Barriers To the Cns For Drug Deliverymentioning
confidence: 99%
“…With the development of microcatheters, IA delivery with distal cannulation of super-selective arteries is now possible; although this may reduce neurologic complications, this comes at the cost of increased streaming effects ( 48 ). In addition, drug delivery is limited to a more precise region, which may not reach the invasive malignant cells at the tumor edge, and only a small percentage (6%) of patients with glioblastoma have a single vessel identified as supplying the tumor ( 51 ). Because most adult malignant gliomas are supratentorial, intracarotid arterial administration techniques can be used.…”
Section: Circumventing Barriers To the Cns For Drug Deliverymentioning
confidence: 99%
“…This has advantages over carotid or vertebral artery infusions because the drug is delivered specifically to the tumor area, avoiding normal tissue and potentially reducing neurotoxicity [27]. However, a recent study reported that only 6% of patients with glioblastoma have a single vessel supplying the tumor [28]. The selective intra-arterial technique has been performed in concert with selective infusion of mannitol; although permeability of the BBB is increased, disruption is nonspecific.…”
Section: Intra-arterial Deliverymentioning
confidence: 99%
“…Tumor neoangiogenesis can be determined by the cerebral blood volume (CBV), which can be calculated from dynamic susceptibility contrast MRI (DSC-MRI) (6,7). The leakiness of GBM vasculature can be detected by the conventional contrast-enhanced MRI following intravenous administration of gadolinium-based contrast agents (8). As a result of diffusion of contrast molecules out of vessels and accumulation within extracellular space in tumors, contrastenhancing hyper-intense regions on T1-weighted (T1W) sequences are presented in nearly all GBM (9).…”
Section: Introductionmentioning
confidence: 99%